PERAN MANAJEMEN HUBUNGAN MASYARAKAT DALAM MEMBANGUN CITRA SEKOLAH DI SMA AL AMIN KABUPATEN BOGOR - Nurjanah, Hera; Hasanah, Tita; Mukri, Rusdiono (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2024)
The school's image represents the reputation of an educational institution in the eyes of the public. The assessment of the community towards the school's image depends on the role of its public relations management. Effective public relations management is necessary in order to achieve a positive school image. This research aims to examine the role of public relations management in building the school's image at Al Amin High School, located in Pamijahan District, Bogor Regency. The research method used is descriptive with a qualitative approach. The data analysis was conducted using the Atlas.ti 9 software. The research findings indicate that the public relations management of Al Amin High School has played a significant role in building the school's image. The study also revealed both supportive and inhibiting factors, as well as the efforts made in establishing a positive image for the school.